Content of Dry Matter, Organic Matter, and Ash Wheat forage (Triticum Spp.) Fodder of Hydroponic at age different Defoliation Times - Putra, Arya Eka; Sukaryani, Sri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The increasing need for green fodder as animal feed continues to increase, especially in the face of limited land and weather changes, this encourages farmers to continue to innovate in an effort to meet the need for green fodder for livestock. Wheat (Triticum spp.) is a potential plant for green fodder because it grows quickly and has high nutritional content. The hydroponic fodder system is one method of plant cultivation that uses water rich in nutrients as a substitute for soil. The purpose of this study was to determine the effect of different defoliation ages on hydroponic wheat fodder green fodder production and nutrient content (dry matter, organic matter, and ash). The design used in the study was a Completely Randomized Design with 3 treatments, each treatment repeated 4 times. The treatments were P1: defoliation at 6 days; P2: defoliation at 8 days and P3: defoliation at 10 days. The variables observed included fresh weight, dry matter content, organic matter, and ash content of hydroponic wheat fodder green fodder. The results of the study showed that the highest fresh weight was achieved in P3 (118.75 ± 3.8 grams), then P2 (104.50 ± 6.1 grams) and P1 (77.50 ± 5 grams). The highest dry matter content was achieved in treatment P1 (33.84 ± 4.99 grams), followed by P2 (27.16 ± 2.9 grams) and the lowest in treatment P3 (23.33 ± 0.7 grams). The lowest ash content was in P1 (1.76 ± 0.39 grams) while the highest organic matter content was in treatment P1 (98.24 ± 0.39 grams). This research can be concluded that the difference in defoliation age between 6 - 10 days has a significant effect on the production and content of dry matter, organic matter and ash of hydroponic fodder.